Alternative Current Electrical Conductivity of Octaphynyl Tetrapyrrazino Porphrazine Cobalt (II) - Hasan Sabeeh Jabur (Journal of Global Pharma Technology, 2018)
The alternative current (Ac) conductivity of octaphynyl tetrapyrrazino porphrazine cobalt (op Tp Pz Co) was measured at rate of frequency of 5 X I03to 5 X103 Hz of and temperature rate (303 to 423) k. The dc conductivity was carry out in the same temperature rate, which consists of frequency independent (Dc conductivity) and frequency dependent part. This type of conductivity results from hopping of cargo carriers between localized sites around Fermi levels. The jump position is indication of the degree of imperfection in the crystal. Crystallization degree the number of the jump position was calculated using Web band William equation which is estimated to be l x l020ev-1cm3.Keywords: Octaphenyl Tetrapyrazino Porphrazine cobalt, Temperature rate (303 to 423) k Frequency dependent, Conductivity Ac, Conductivity.